CPX-351 versus 7+3 cytarabine and daunorubicin chemotherapy in older adults with newly diagnosed high-risk or secondary acute myeloid leukaemia: 5-year results of a randomised, open-label, multicentre, phase 3 trial. Issue 7 (July 2021) - Lancet, Jeffrey E; Uy, Geoffrey L; Newell, Laura F; Lin, Tara L; Ritchie, Ellen K; Stuart, Robert K; Strickland, Stephen A; Hogge, Donna; Solomon, Scott R; Bixby, Dale L; Kolitz, Jonathan E; Schiller, Gary J; et al.
Summary: Background: Daunorubicin and cytarabine are used as standard induction chemotherapy for patients with acute myeloid leukaemia. CPX-351 is a dual-drug liposomal encapsulation of daunorubicin and cytarabine in a synergistic 1:5 molar ratio. Primary analysis of the phase 3 trial in adults aged 60–75 years with newly diagnosed high-risk or secondary acute myeloid leukaemia provided support for approval of CPX-351 by the US Food and Drug Administration and European Medicines Agency. We describe the prospectively planned final 5-year follow-up results. Methods: This randomised, open-label, multicentre, phase 3 trial was done across 39 academic and regional cancer centres in the USA and Canada. Eligible patients were aged 60–75 years and had a pathological diagnosis of acute myeloid leukaemia according to WHO 2008 criteria, no previous induction therapy for acute myeloid leukaemia, and an Eastern Cooperative Oncology Group performance status of 0–2. Patients were randomly assigned 1:1 (stratified by age and acute myeloid leukaemia subtype) to receive up to two induction cycles of CPX-351 (100 units/m 2 administered as a 90-min intravenous infusion on days 1, 3, and 5; on days 1 and 3 for the second induction) or standard chemotherapy (cytarabine 100 mg/m 2 per day continuous intravenous infusion for 7 days plus intravenous daunorubicin 60 mg/m 2 on days 1, 2, and 3 [7+3]; cytarabine for 5 days and daunorubicin on days 1 and 2 for the second induction [5+2]). Patients with complete remission or complete remission with incomplete neutrophil or platelet recovery could receive up to tw cycles of consolidation therapy with CPX-351 (65 units/m 2 90-min infusion on days 1 and 3) or chemotherapy (5+2, same dosage as in the second induction cycle). The primary outcome was overall survival analysed in all randomly assigned patients. No additional adverse events were collected with long-term follow-up, except data for deaths. This trial is registered with ClinicalTrials.gov, NCT01696084, and is complete. Findings: Between Dec 20, 2012, and Nov 11, 2014, 309 patients with newly diagnosed high-risk or secondary acute myeloid leukaemia were enrolled and randomly assigned to receive CPX-351 (153 patients) or 7+3 (156 patients). At a median follow-up of 60·91 months (IQR 60·06–62·98) in the CPX-351 group and 59·93 months (59·73–60·50) in the 7+3 group, median overall survival was 9·33 months (95% CI 6·37–11·86) with CPX-351 and 5·95 months (4·99–7·75) with 7+3 (HR 0·70, 95% CI 0·55–0·91). 5-year overall survival was 18% (95% CI 12–25%) in the CPX-351 group and 8% (4–13%) in the 7+3 group. The most common cause of death in both groups was progressive leukaemia (70 [56%] of 124 deaths in the CPX-351 group and 74 [53%] of 140 deaths in the 7+3 group). Six (5%) of 124 deaths in the CPX-351 group and seven (5%) of 140 deaths in the 7+3 group were considered related to study treatment. Interpretation: After 5 years of follow-up, the improved overall survival with CPX-351 versus 7+3 was maintained, which supports the previous evidence that CPX-351 can contribute to long-term remission and improved overall survival in patients aged 60–75 years with newly diagnosed high-risk or secondary acute myeloid leukaemia. Funding: Jazz Pharmaceuticals.